Clinicopathologic and Prognostic Significance of Metalloproteinase Tissue Inhibitor-2 Promoters in Tunisian Colorectal Cancer: A Case-Control Study. Issue 8 (September 2016) - Ben Néjima, Dalel; Ben Zarkouna, Yosr; Pujol, Pascal; Gammoudi, Amor; Boussen, Hamouda; Manai, Mohamed
Abstract : Tissue inhibitors of metalloproteinases (TIMPs) appear to affect many aspects of cancer biology, playing a crucial role in cell signaling by regulating cell growth, apoptosis, invasion, metastasis, angiogenesis, and genomic instability. In the present study, we investigate whether TIMP-2 SNP, TIMP-2 mRNAs, and TIMP-2 protein is associated with susceptibility to colorectal cancer (CRC) in Tunisian population. Taqman and DNA sequencing techniques were used for genotyping, TIMP-2 expression of each genotype was analyzed using semiquantitative RT-PCR and TIMP-2 protein expression was analyzed using immunohistochemistry staining. Our results showed that significantly elevated CRC risk was found in individuals with CC genotype (odds ratio 1.959; 95% confidence interval, 1.055-3.637). Moreover TIMP-2 mRNA expression in the colorectal cell carcinomas was significantly higher compared with the normal colorectal tissue (0.487±0.015 vs. 0.210±0.013) ( P <0.05). In addition, serum levels of TIMP-2 were significantly lower in CRC patients than in adenoma patients ( P =0.01) and healthy controls ( P =0.003). Serum levels of TIMP-2 correlated significantly with tumor stage and TNM stage and were the lowest in CRC patients with stage D, T4, (N1, N2, N3), M(+). In conclusion, our study demonstrate for the first time the distribution and the clinical significance of TIMP-2 promoter polymorphisms, mRNA, protein expression, and serum level in CRC Tunisian patients suggesting that the genotyping and serum level of TIMP-2 as potential markers for susceptibility to CRC will allow a precise and early identification of individuals at high risk and will aid the design of therapeutic modalities and evaluation of treatment outcome.